Does Abrupt Weight Loss Caused by Bariatric Surgery Compromise the Voice in Women? - Bosso, Janaina Regina [UNESP]; Tavares, Elaine Lara Mendes [UNESP]; Rodrigues, Sergio Augusto [UNESP]; Martins, Regina Helena Garcia [UNESP] (Elsevier, 2021)
Objective: To evaluate vocal symptoms, voice characteristics and videolaryngoscopy in obese women before and after bariatric surgery. Methods: Obese patients (18 to 59 years old), candidates for bariatric surgery were recruited. Evaluation times: T1 (preoperative), T2 (after six months), T3 (after 12 months). Evaluated parameters: weight, height, body mass index, abdominal and neck circumference, vocal self-assessment, perceptual and acoustic vocal assessment, and videolaryngoscopy. Results: A total of 37 obese women were included, average age 40.8 years. There was a decrease in anthropometric measurements between the preoperative assessment and after 12 months: weight (121.18 ± 15.4 kg; 77.1 ± 11.6 kg), BMI (46.6 ± 6.95 kg/m2; 30 ± kg/m2), abdominal circumference (128 ± 16.1; 99.1 ± 12.1), and neck circumference (41.1 ± 5.85; 36.6 ± 3.02). Gastroesophageal (21.6%) and vocal symptoms (27%) prevailed. No difference was identified in vocal self-assessment between the evaluations. In the acoustic analysis, f0 increased and the soft phonation index decreased. The perceptual analysis registered lower scores for the degree of dysphonia (G) and voice instability (I). The maximum phonation time values increased without changing the s/z ratio. Videolaryngoscopies showed a posterior middle cleft and improvement in the signs of reflux. Conclusions: Bariatric surgery led to an important and gradual decrease in anthropometric parameters. The voice became less hoarse, with higher pitch and more stable, with an improvement in maximum phonation time, however with slight breathiness. Such changes were not noticed by the patients.
Keywords: Bariatric surgery; Dysphonia; Voice; Weight loss